(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Due to the sheet metal bending process, the sheet of metal is forced to take the shape of the die cavity by a rigid punch to fit it with that cavity dimensions, but when the punch is removed, the elastic deformation will be released and only the plastic deformation will be remained, this release of the elastic deformation caused the phenomenon which is called springback defect. The springback is one of the defects that happen in the forming of sheet metal and its effect appears clearly in the assembly processes because of the change in final product dimensions. More researches were done to reduce the effect of this phenomenon on the uniform and symmetry sheets, but in reality, the products which are made by bending the sheet metal may contain holes before its forming. Therefore, in this research, the effect of the hole size and its center locations on the springback behavior and its value was specified for carbon steel material with (200 x 50 x0.75) mm, which and was drilled with different holes diameters (5, 10, 15, 20, 25) mm, and then the location of each hole was changed about the perpendicular centerline of each sheet . Design of Experiment Software DOE was used to predict the value of springback for two V-shaped dies with forming depth of 12 and 19 mm by conducting 78 experimental tests and feeding its results as an input to DOE to select the perfect mix between hole size and its position which gives the minimum springback effect. Two mathematical quadratic models were built for the two die depths in terms of use input parameters. It was found that both hole size and its location had great impact on the springback. The optimum values of springback were obtained for the two die depths. Good agreement was found between the experimental and theoretical springback with a maximum error of 0.286 % for 12 mm die depth and 0.037 % for 19 mm die depth. Finally, it was concluded that the springback value was reduced by 6.47 % when using 19 mm die depth in comparison with 12 mm depth.